2008
DOI: 10.1103/physrevd.77.045024
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of the relativistic fluid in physical phase space on Kähler manifolds

Abstract: We discuss the quantization of a class of relativistic fluid models defined in terms of one real and two complex conjugate potentials with values on a Kähler manifold, and parametrized by the Kähler potential K(z, z) and a real number λ. In the hamiltonian formulation, the canonical conjugate momenta of the potentials are subjected to second class constraints which allow us to apply the symplectic projector method in order to find the physical degrees of freedom and the physical hamiltonian. We construct the q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This type of commutative fluids has been discussed in [37] in the Kähler parametrization, while in [43] it was shown that they can be quantized using canonical methods. Then the equation (35) takes the following simpler form…”
Section: Plane Waves In Noncommutative Fluids In Snyder Spacementioning
confidence: 99%
See 1 more Smart Citation
“…This type of commutative fluids has been discussed in [37] in the Kähler parametrization, while in [43] it was shown that they can be quantized using canonical methods. Then the equation (35) takes the following simpler form…”
Section: Plane Waves In Noncommutative Fluids In Snyder Spacementioning
confidence: 99%
“…The choice of the commutative fluid potentials is not unique. When it is made in terms of real functions θ(x), α(x) and β(x) it is called the Clebsch parametrization [35,36] while the fluid potentials given in terms of one real θ(x) and two complex functions z(x) andz(x), respectively, define the so called Kähler parametrization [37,38,39,40,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in [16], the description of the fluid degrees of freedom in terms of fluid potentials allows one to lift the obstruction to inverting the symplectic form in the canonical phase space of the fluid variables. (For other applications of the Kähler parametrization of the fluid potentials see [18,20,21,22,23,24,25]. )…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of the constraints (9) to the classical theory were analyzed in [8]. In [14] the above results were derived by a different method and the system was quantized for the particular choice K(z,z) = zz and f (ρ) ∼ ρ 2 by applying the canonical quantization method.…”
Section: Relativistic Fluid In the Kähler Parametrizationmentioning
confidence: 99%
“…Therefore, it is certainly interesting to understand the quantum systems that correspond to these models. In [14] we have quantized a simple fluid characterized by the Kähler potential of the complex plane K(z,z) = zz and by the function f (ρ) ∼ ρ 2 by applying the canonical quantization methods of the Quantum Field Theory.…”
Section: Introductionmentioning
confidence: 99%